The CYP1A2 -163C>A polymorphism does not alter the effects of caffeine on basketball performance - Puente, C.; Abian-Vicen, J.; Del Coso, J.; Lara, B.; Salinero, J. J. (PLOS ONE, 2018)
The aim of this investigation was to analyze the influence of the genetic variations of the -163C>A polymorphism of the CYP1A2 gene on the ergogenic effects of caffeine in elite basketball players. Methods: Nineteen elite basketball players (10 men and 9 women) ingested 3 mg·kg-1 of caffeine or a placebo 60 min before performing 10 repetitions of the following series: the Abalakov jump test followed by the Change-of-Direction and Acceleration Test (CODAT). The players then competed in a 20-min simulated basketball game. Self-perceived performance and side effects were recorded by questionnaires after the trials. The effects of caffeine on basketball performance were established according to players` CYP1A2 genotype (rs762551): AA homozygotes (n = 10) and C-allele carriers (n = 9). Results: In the 10 repetitions, caffeine increased Abalakov jump height by a mean of 2.9±3.6% in AA homozygotes (p = 0.03) while this effect did not reach statistical significance for C-allele carriers (2.3 ± 6.8%; p = 0.33). Caffeine did not affect sprint time in the CODAT test in either genotype group but it increased the number of impacts performed during the simulated game in both AA homozygotes (4.1 ± 5.3%; p = 0.02) and C-allele carriers (3.3 ± 3.2%; p = 0.01). During the 24 h following the test, AA homozygotes tended to experience increased insomnia with caffeine while C-allele carriers did not present this effect. The remaining variables were unaffected by the genotype. Conclusion: The CYP1A2 -163C>A polymorphism minimally altered the ergogenicity derived from the consumption of a moderate dose of caffeine in elite basketball players.